2022
DOI: 10.1101/2022.09.12.22279860
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Exercise prescription and strategies to promote the cross-education of strength: a scoping review

Abstract: doi: medRxiv preprint NOTE: This preprint reports new research that has not been certified by peer review and should not be used to guide clinical practice.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 85 publications
0
6
0
Order By: Relevance
“…There is considerable variability in how cross-education has been implemented with respect to exercise type, intensity, muscle group, contraction type and training volume. Despite the limited literature, by emphasising targeted and effective cross-education,8 we contend that cross-education provides a promising low-risk adjunct approach to facilitate early-stage ACLR rehabilitation. Randomised clinical trials carefully investigating the efficacy of cross-education for ACLR rehabilitation are needed.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…There is considerable variability in how cross-education has been implemented with respect to exercise type, intensity, muscle group, contraction type and training volume. Despite the limited literature, by emphasising targeted and effective cross-education,8 we contend that cross-education provides a promising low-risk adjunct approach to facilitate early-stage ACLR rehabilitation. Randomised clinical trials carefully investigating the efficacy of cross-education for ACLR rehabilitation are needed.…”
Section: Discussionmentioning
confidence: 87%
“…Many features of cross-education interventions for ACLR have not been adequately researched 8. There is considerable variability in how cross-education has been implemented with respect to exercise type, intensity, muscle group, contraction type and training volume.…”
Section: Discussionmentioning
confidence: 99%
“…A number of factors likely contribute to the conflicting results, including the muscle groups trained (Manca et al 2017), but the prescription of higher relative loads in the current study is considered pivotal. With numerous studies demonstrating greater cross-education benefits training with heavier loads (Pelet and Orsatti 2021;Voskuil et al 2023), the recommendation to train at high intensities (≥ 90% of 1-RM) is likely more important when aiming to generate a cross-education stimulus in previously trained muscles. However, more research is needed to better understand the cross-education training requirements to attenuate detraining effects in muscles that cease training.…”
Section: Discussionmentioning
confidence: 99%
“…In support of this theory, a recent study has reported that unilateral leg extensor training prescribed at increasing weekly loads (70-85% of one-repetition maximum [1-RM] for 4 weeks) was unable to maintain muscle strength and power in the contralateral leg extensors of recreationally engaged older women (> 60 years) (de Souza Teixeira et al 2023). With numerous studies demonstrating greater cross-education benefits training with heavier loads (Pelet and Orsatti 2021;Voskuil et al 2023), the question of whether unilateral strength training prescribed at higher intensities is effective in the reduction of detraining effects is still open. This finding is important for athletes and otherwise-active populations who have become injured as well as for clinical practitioners who use exercise 'prehabilitation' to improve the recovery rate of their patients from a pre-planned surgery.…”
Section: Introductionmentioning
confidence: 99%
“…In a different study, applying stimulation at an intensity of 65% isometric strength also yielded a 21% strength increase in the contralateral limb muscle [ 33 ]. Thus, as suggested in a recent review [ 36 ], unilateral exercise intensity is one of the key factors in inducing cross-education. Additionally, our three-week training sessions were also relatively short when compared to previous investigations (e.g., 6 weeks) [ 17 ].…”
Section: Discussionmentioning
confidence: 99%